A tale of two populations: surviving and destroyed dwarf galaxies and the build-up of the Milky Way's stellar halo. Issue 4 (6th August 2020) - Fattahi, Azadeh; Deason, Alis J; Frenk, Carlos S; Simpson, Christine M; Gómez, Facundo A; Grand, Robert J J; Monachesi, Antonela; Marinacci, Federico; Pakmor, Rüdiger
ABSTRACT: We use magnetohydrodynamical simulations of Milky Way-mass haloes from the Auriga project to investigate the properties of surviving and destroyed dwarf galaxies that are accreted by these haloes over cosmic time. We show that the combined luminosity function of surviving and destroyed dwarfs at infall is similar in the various Auriga haloes, and is dominated by the destroyed dwarfs. There is, however, a strong dependence on infall time: destroyed dwarfs typically have early infall times of less than 6 Gyr (since the big bang), whereas the majority of dwarfs accreted after 10 Gyr have survived to the present day. Because of their late infall, the surviving satellites have higher metallicities at infall than their destroyed counterparts of similar mass at infall; the difference is even more pronounced for the present-day metallicities of satellites, many of which continue to form stars after infall, in particular for $M_{\rm star}\gt 10^7 \, {\rm M}_\odot$ . In agreement with previous work, we find that a small number of relatively massive destroyed dwarf galaxies dominate the mass of stellar haloes. However, there is a significant radial dependence: while 90 per cent of the mass in the inner regions (${\lt}20\, $  kpc) is contributed, on average, by only three massive progenitors, the outer regions (${\gt}100\, $  kpc) typically have ∼8 main progenitors of relatively lower mass. Finally, we show that a few massive progenitors dominate the metallicity distribution of accreted stars, even at the metal-poor end. Contrary to common assumptions in the literature, stars from dwarf galaxies of mass $M_{\rm star}\lt 10^7 \, {\rm M}_\odot$ make up less than 10 per cent of the accreted, metal poor stars ([Fe/H] ${\lt}-3$ ) in the inner $50\, $  kpc.